Recent trends in wearable device used to detect freezing of gait and falls in people with Parkinson’s disease: A systematic review - Huang, Tinghuai; Li, Meng; Huang, Jianwei (Frontiers in Aging Neuroscience, 2023)
Background: The occurrence of freezing of gait (FOG) is often observed in moderate to last-stage Parkinson’s disease (PD), leading to a high risk of falls. The emergence of the wearable device has offered the possibility of FOG detection and fall of patients with PD allowing high validation in a low-cost way. Objective: This systematic review seeks to provide a overview of existing literature to establish the forefront of sensors type, placement and algorithm to detect FOG and falls. Methods: Two electronic databases were screened by title and abstract to summarize the state of art on FOG and fall detection with any wearable technology among patients with PD. To be eligible for inclusion, papers were required to be full-text articles published in English, and the last search was completed on September 26, 2022. Studies were excluded if they; i) only examined cueing function for FOG, ii) only used non-wearable devices to detect or predict FOG or falls, iii) did not provide sufficient details about the study design and results. A total of 1748 articles were retrieved from two databases. However, only 75 articles were deemed to meet the inclusion criteria according to the title, abstract and full-text reviewed. Variable was extracted from chosen research, including authorship, details of the experimental object, type of sensor, device location, activities, date of publication, the algorithm and detection performance. Results: A total of 75 papers were selected for data extraction. There were wide varieties of the studied population (from 1 to 131), type of sensor, placement and algorithm. The thigh and ankle were the most popular device location, and the combination of accelerometer and gyroscope was the most frequently used inertial measurement unit (IMU). The results also show that increasingly complex machine-learning algorithms have become the trend in FOG and fall detection. Conclusion These data support the application of the wearable device to access FOG and falls among patients with PD and controls. Future work should consider an adequate sample size, and the experiment should be performed in a free-living environment. Moreover, a consensus on provoking FOG/fall, methods of assessing validity and algorithm are necessary.